Motor Examination in the Diagnosis of Carpal Tunnel Syndrome - Neral, Mithun; Imbriglia, Joseph E.; Carlson, Lois; Wollstein, Ronit (Journal of Hand and Microsurgery, 2017)
The relative importance and use of motor evaluation to diagnose carpal tunnel syndrome (CTS) is not clear. Because the ulnar nerve is not affected in CTS, we evaluated comparing the strength of the median-nerve innervated muscles to the ulnar innervated muscles in the same patient, through manual muscle testing (MMT) and a handheld dynamometer. Our purpose was to evaluate whether this method, which takes into account patient-dependent factors that would affect both groups of muscles equally, can provide better assessment of CTS. A retrospective case-control review of MMT and dynamometer-measured strength for CTS was performed. The study was performed retrospectively but prior to surgery or other treatment. There were 28 cases (CTS) and 14 controls (without CTS). Positive nerve conduction tests defined cases. MMT of the thenar musculature was found to be unreliable as a test for CTS. Comparisons to ulnar nerve innervated muscle strength did not improve sensitivity or specificity of the MMT examination. Use of the dynamometer improved sensitivity and specificity of motor testing in CTS over MMT. Motor evaluation is important for the diagnosis of CTS, but further study is warranted, specifically to define the method of motor evaluation and delineate the subgroup of patients (predominantly thenar motor presentation) that would benefit most from motor testing and motor-focused treatment.
Keywords: carpal tunnel syndrome; diagnosis; dynamometer; motor examination; ulnar